PENINGKATAN AKTIVITAS BELAJAR DALAM MENYELESAIKAN SOAL YANG BERVARIASI MELALUI SISTEM PEMBERIAN TUGAS RUMAH DAN DISKUSI DI SMA NEGERI 1 LUHAK NAN DUO - Mila Handayani (JURNAL MANAJEMEN PENDIDIKAN, 2019)
In carrying out learning the teacher must design and conduct learning efficiently, creatively, appear attractive and authoritative as an actor in front of the class, and the results must meet quality standards. Problems faced by teachers can be in the form of problems in class, or individual problems of students. Problems in class can be discussed internally and externally from students. Internal factors include: learning motivation, intelligence, habits and self-confidence. To improve student motivation, the teacher can create a pleasant learning atmosphere. One of them is by giving home assignments and discussions. The homework assignment and discussion are expected to grow students' motivation and activities and can create a pleasant classroom atmosphere in the process of chemical learning. For that research carried out directly in the practice of learning, where certain actions are carried out based on the problems in the field that must be addressed immediately. This research was conducted at SMAN 1 Luhak Nan Duo with a sample of class X MIA 3 academic year 2018/2019. Action research consists of two cycles where each cycle consists of 4 meetings. The data analysis technique in this study was to look at student learning activities in the teaching and learning process, the results of observation were analyzed by determining the percentage of each activity. From the results of this study it was found that the increase in student activity by giving home assignments and discussions was more effective and time-saving.